Pangan Fungsional Berbasis Susu dan Produk Turunannya - Fitri Suciati; Laras Sirly Safitri (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2021)
Milk is food that contains complete nutrients that are consumed by various groups. Milk contains macronutrients such as protein, fat and carbohydrates as well as micronutrients such as vitamins and minerals and other components that are useful for human nutritional and health needs. Apart from containing micro and macronutrients, milk and its derivative products also contain bioactive components that have certain physiological functions that are beneficial to health, which are called Functional Foods. Milk-based functional food and its derivatives have bioactive components such as bioactive peptides, prebiotics, probiotics, conjugated linoleic acid (CLA) and several other bioactive components. Milk and its derivative products such as cheese, yogurt, kefir, and other derivative products have the potential to be developed. The development of milk-based food into functional food is expected to reduce the risk of degenerative diseases such as obesity, coronary heart disease, hypertension and cancer.